Physicochemical characteristics of ashes deposited on a wall flow diesel particulate filter of compression ignition engine - Sattatad Rodvanna; Mek Srilomsak; Chaiwat Nuthong; Chinda Charoenphanich; Manop Masomtob; Peerawat Saisirirat; Nuwong Chollacoop; Katsunori Hanamura; Preechar Karin (My University, 2023)
The investigation of physicochemical characteristics of metal oxide ashes, deposited on a diesel particulate filter, was conducted using electron microscopy, energy dispersive spectroscopy, X-Ray fluorescence, and X-Ray diffractometry techniques. Iron is the main component of deposited ash on the DPF, and other ash components consisted of elements such as silicon, calcium, copper, sulfur, phosphorus, zinc, aluminum and minor chromium. It was clarified that this metal oxide ash has catalytic effect that contributed to an enhancement of soot oxidation. The apparent activation energies of soot oxidation on SiC powder and metal oxide ashes powder are approximately 169 and 135 kJ/mol, respectively.
Keywords: Catalytic Processes in Materials Science